New heterodontosaurid remains from the Cañadón Asfalto Formation: cursoriality and the functional importance of the pes in small heterodontosaurids. (27th June 2016) - Becerra, Marcos G.; Pol, Diego; Rauhut, Oliver W.M.; Cerda, Ignacio A.
Abstract: New ornithischian remains reported here (MPEF-PV 3826) include two complete metatarsi with associated phalanges and caudal vertebrae, from the late Toarcian levels of the Cañadón Asfalto Formation. We conclude that these fossil remains represent a bipedal heterodontosaurid but lack diagnostic characters to identify them at the species level, although they probably represent remains of Manidens condorensis, known from the same locality. Histological features suggest a subadult ontogenetic stage for the individual. A cluster analysis based on pedal measurements identifies similarities of this specimen with heterodontosaurid taxa and the inclusion of the new material in a phylogenetic analysis with expanded character sampling on pedal remains confirms the described specimen as a heterodontosaurid. Finally, uncommon features of the digits (length proportions among nonungual phalanges of digit III, and claw features) are also quantitatively compared to several ornithischians, theropods, and birds, suggesting that this may represent a bipedal cursorial heterodontosaurid with gracile and grasping feet and long digits. In particular, the elongated non-terminal pedal phalanges and morphology of digit III resemble features present in arboreal birds, a unique condition found so far among ornithischians.